Genealogi Kajian Hadis Ulama al-Banjari - Hanafi Hanafi (Institut Agama Islam Negeri (IAIN) Salatiga, 2017)
Since the 16th century, Middle East became a scientific destination for the scholars of Nusantara. The network of Middle Eastern scholars has contributed greatly to the development of various Islamic intellectual traditions in the archipelago, even the case happened in Banjar society. In the process of transmitting scholars, the scholars of al-Banjari (scholars from Banjar, South Kalimantan) are heavily influenced by Islamic ideas derived therein, including kalam, jurisprudence, tasawwuf, and hadith studies. This article will prove to what extend the influence of Middle Eastern scholars on the development of intellectual traditions of al-Banjari scholars in the study of hadith is. The research method in this paper is by reading the primary sources, in the form of Hadith texts by al-Banjari scholars, and then the genealogy of the sanad and their Hadith diplomas connected with the scholars of hadith study in the Middle East. The reading of the sanad and the certificate will prove that their scholarship is connected to authoritative scholars of hadith. Al-Banjari scholars who became the research object is a scholar from the tribe of Banjar which has a script in the field of hadith or hadith study using Arabic or Malay Arabic. From the standardization used, seven scholars became the object of the research, namely Muhammad Arsyad al-Banjari, Muhammad Kasyful Anwar, Muhammad Anang Sya’rani Arif, Abdul Wahid, Muhammad Syukeri Unus, Fahmi Zamzam, and Muhammad Nurdin Marbu.